Multi-word ideologemes in the focus of Russian linguistic culture: corpus study - Svetlana N. Starodubets; Sergei M. Pronchenko; Olga V. Belugina (Russian Language Studies)
The relevance of the study lies in the connection between public ideological guidelines and national culture, the state language. The latter is both a means of interethnic communication and an instrument for comprehending values and ideological priorities in the society. A linguistic-cultural study of ideologemes records axiological guidelines that form conceptual and linguistic pictures of the world. The aim of the study is to study the specific semantic field and the communicative meaning of three-component ideologemes which have not previously been the subject of scientific study Russian national consciousness, Russian national culture, Russian national anthem / flag . The form and the content of these ideologemes in modern Russian language were analyzed on the material of the main corpus of Russian National Corpus. The context syntagmatics and political discourse paradigmatics were also considered, so their representative invariants and variants were identified. This study used frame representation methodology; as a result, the content plan of the analyzed compound names was established. Thus, the ideologeme Russian national consciousness has three orthographic variants; Russian national culture , three; Russian national anthem / flag , two. The content of the linguistic units is based on the following communicative meanings: (a) ‘the process of reflecting reality in human consciousness through the prism of Russian national mentality’; (b) ‘the totality of Russian national achievements through the prism of historical, cultural, religious, and political views’; (c) ‘a piece of music as a symbol of Russian national statehood’ / ‘a canvas as a symbol of Russian national statehood’. The semantic fields of three-component ideologemes are characterized, evaluative explicators (non-evaluative, meliorative, and pejorative ones) are revealed, communicative meanings are formulated. The research prospects which involve identifying relevant ideologemes and analyzing the mechanisms of ideologizing the semantics of compound names in the mental and symbolic pictures of the world of a modern Russian linguistic personality are outlined.